What Potential Entrepreneurs from Generation Y and Z Lack-IEO and the Role of EE - Julita Eleonora Wasilczuk; Anita Richert-Kaźmierska (MDPI AG, 2020)
This paper addresses the issue of individual entrepreneurship orientation (IEO) and entrepreneurship education (EE), which are both important for modern economic development. Intergenerational differences in these areas were discussed, especially characteristics of Generations Y and Z. The results of research conducted among 757 Polish students showing their IEO are presented. 80% of respondents displayed high levels of proactivity (primarily directed at meeting their own needs), whilst only 56% exhibited innovativeness and only 47% risk-taking. On the basis of the research results, the authors formulated recommendations for entrepreneurship education, aimed at strengthening IEO among representatives of Generations Y and Z.